Juvenile delinquency: mainstream and crosscurrents - Fuller, John R. (Pearson, Prentice-Hall)
What is a juvenile delinquent? -- The development of social control -- Measuring delinquency -- International and comparative delinquency -- Theoretical foundations of crime and delinquency -- Biological and psychological theories of delinquency -- Sociological theories of delinquency -- Critical, life course, and integrated theories -- Female delinquency -- The family and delinquency -- Schools and delinquency -- Youth gangs and delinquency -- The police -- The juvenile court -- Juvenile corrections -- The future of delinquency and juvenile justice